PEMBERIAN BEBERAPA AMELIORAN TERHADAP PERUBAHAN SIFAT KIMIA TANAH GAMBUT - ERVINA ARYANTI; YULITA YULITA; AULIA RANI ANNISAVA (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
The research was conducted in the Faculty of Agriculture and Animal Science State University of Sultan Syarif Kasim Riau. This research aimed to determine best ameliorant which can increase the chemical content of peat soil such as pH, N, P, K and decrease C, C/N. The research used random sampling method, there are: without ameliorant, chicken manure fertilizer, compost of oil palm empty fruits bunches, rice husk ash, and bunch ash. The results showed that give rice husk ash and dolomite can increase some nutrient content of peat. Based on result of the research rice husk ash can increase P from lowest to highest criteria. Giving dolomite increase best pH value, from sour to neutral.